Penguatan Persepsi Silvofishery pada Pembudidaya Kerang Darah di Kawasan Mangrove Tanjung Punai, Kabupaten Bangka Barat, Kepulauan Bangka Belitung - Kurniawan, Ardiansyah; Triswiyana, Ira; Aji A Kurniawan, Ahmad (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2022)
Tanjung Punai, in the western of Bangka Island, has a 1988.74 ha of mangrove forest with dominanceon the type of Sonneratia Alba. Most of the local population works are caught shrimp and crab, buthaving a side business cultivating blood shells on the mud beach around the mangrove. There areconcerns about the conversion of mangrove land for ponds and the increasing area of blood shellfishcultivation. For this reason, it is necessary to strengthen information about mangrove benefits andsilvofishery systems' cultivation. Submission of information and knowledge of silvofishery and theimportance of mangrove protection is made through group discussions or individuals of clampers.Knowledge of the benefits of mangroves for the sustainability of shellfish cultivation and the capture ofshrimp and crabs can be accepted and approved by cultivators. Silvofishery's concept for blood shellfishcultivation if the expansion of the land leads to the mangrove area is also understood.